2011
DOI: 10.1016/j.jip.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Musty odor of entomopathogens enhances disease-prevention behaviors in the termite Coptotermes formosanus

Abstract: Termites often eliminate pathogens directly through mutual grooming, and are thereby prevent infections from entomopathogenic fungi. Our previous study confirmed that the antennae of Coptotermesformosanus sensitively responded to the musty odor of entomopathogenic fungi. However, it is unclear if this odor has any effect on termite behavior. The purpose of this study was to clarify the effects of fungal odor on termite behavior, especially on conidia removal. The musty odor was prepared as an aqueous solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…In flies, specific olfactory receptors are devoted to the detection of harmful microbes (Stensmyr et al, 2012). In termites, we have shown that odors from pathogenic spores are detected by the olfactory system (Yanagawa et al, 2009) and that such odors trigger allo-grooming (Yanagawa et al, 2010, 2011, 2012). This opens the possibility that contact chemicals related to microbes could also trigger grooming in insects.…”
Section: Introductionmentioning
confidence: 99%
“…In flies, specific olfactory receptors are devoted to the detection of harmful microbes (Stensmyr et al, 2012). In termites, we have shown that odors from pathogenic spores are detected by the olfactory system (Yanagawa et al, 2009) and that such odors trigger allo-grooming (Yanagawa et al, 2010, 2011, 2012). This opens the possibility that contact chemicals related to microbes could also trigger grooming in insects.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports, which suggested that more virulent isolates could repel termites more strongly [32], [33], also support this finding. On the other hand, an increase in grooming behavior induced by a musty odor occurred independent of virulence [34]. In addition, the termite aversion to fungal odor gradually increased with an increase in the conidia concentration in the high-virulence isolates of Beauveria and Isaria.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, due to the new absorption method with a MonoTrap disc, we could collect more chemicals than with SPME [34]. In this analysis, no common volatile was associated with fungal virulence or species.…”
Section: Discussionmentioning
confidence: 99%
“…The VOCs of Metarhizium and other fungi are repellents for several invertebrates including store grain pests ( Sitophilus zeamais Motschulsky) , and termites ( Coptotermes formosanus Shiraki) . Repellency is dependent upon the target since some insects are tolerant of higher quantities than others.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Most notable are 1-octen-3-ol, 3-octanone and 1-octene, which are produced by a wide range of fungi including saprophytic molds, mushrooms and entomopathogenic fungi including species of Beauveria and Metarhizium. [24][25][26][27][28] Exactly why entomopathogenic fungi produce these compounds is unclear but the fact that so many insects exhibit avoidance behavior suggest that they are responding to VOCs. 20,29 This paper reports that these compounds are highly repellent or toxic to slugs and snails.…”
Section: Introductionmentioning
confidence: 99%